Maquet osteotomy for isolated patellofemoral arthritis, a forgotten surgical technique - Danisman, Murat; Bozoglan, Muhammet; Demir, Tugcan (Annals of Medical Research, 2022)
Aim: The focus of this study is to publish the results of Maquet osteotomy for patients who are classified as physiologically young and suffering from anterior knee pain which is unresponsive to conservative treatment. Materials and Methods: We performed a retrospective review of 11 consecutive patients (5 [45.5%] males, 6 [54.5%] females; mean age, 51.8 years) who underwent Maquet osteotomy for isolated patellofemoral osteoarthritis between May 2017 and August 2018. Thirteen osteotomies were performed in 11 patients; 2 patients underwent bilateral procedures. All patients were clinically rated before surgery and at the final follow-up using International Knee Documentation Committee Subjective Knee Evaluation Form (IKDC 2000) and the Kujala Anterior Knee Pain Scale. Also complications were reported. Results: The median follow-up duration was 25 (range=19-33) months. The median preoperative IKDC score was 50 (range = 42-54) points, which had increased to 67 (range=61-72) points at the final follow-up visit (p<.001). The median preoperative Kujala score was 59 (range=48-65) points, which had increased to 77 (range = 67-86) points at the final follow-up (p<.001). We observed 1 major and 1 minor complication in 13 procedures. Conclusion: Although it looks like an extensile surgery, Maquet osteotomy is applicable, safe, easy and a strong alternative for arthroplasty in patellofemoral arthritis.